Toxic jellyfi sh situation in Thailand - Thaikruea, Lakkana; Siriariyaporn, Potjaman; Wutthanarungsan, Rochana; Smithsuwan, Punnarai (Biomedical Sciences and Clinical Medicine, 2024)
This study aimed to describe the toxic jellyfish situation in Thailand. With ad hoc surveillance set up along Thai coastlines, a prospective study was conducted in four provinces to investigate new cases of toxic jellyfish envenomation. Hospitals and health centers were selected for a medical record review to assess morbidity and mortality. The results showed that at least 38 cases of toxic jellyfish were detected by the ad hoc surveillance. There were 381 cases of morbidity and mortality, their median age was 28 years, and 52% of them were foreigners. There was one case of death. The three most common areas of injury were the leg/knee/thigh (40%), arm/forearm/elbow (35%), and ankle/foot (13%). Three of the most common clinical signs were erythema (64%), rash (31%), and edema (26%). Common symptoms included pain (58%), burning sensation (45%), itching (15%), chest tightness (13%), and abdominal pain (10%). The box jellyfish is a health problem in Thailand.